Retos en el perfil profesional del periodista ante la transformación digital - Pérez Moncada, Brigette Stefanía (Machala : Universidad Técnica De Machala, 2021)
The present degree work is motivated, because with the digital evolution there are changes in the profile of the different communication professionals; In the case of journalistic work, it faces a redefinition in its profile linked to the transformations generated by the evolution of Information and Communication Technologies (ICT) and as a consequence digital convergence, which implies that there is a domain of new languages , competencies, knowledge, skills and behaviors, that is why it is important to know them are those challenges of journalists in the province of El Oro, where digital journalism has taken a lot of ground. Taking into account the aforementioned, the investigation called "Challenges in the professional profile of the journalist in the face of digital transformation", has as its main objective to evaluate the current challenges of the journalist, in the face of the digital transformation that has generated a redefinition in his professional profile and as objectives Specific: identifying the competences and capacities of journalists, knowing the needs of professionals and the actions taken to carry out their work, and identifying the challenges they have assumed in their professional profile in the face of digital transformation. For the epistemological theoretical foundation, which is taken as a reference for the research support, the following topics are addressed: digital transformation in journalism, stages of technological transformation in journalism with web 1.0, web 2.0, web 3.0 and web 4,0, the challenges of journalism, the professional-academic profile of the journalist in the digital transformation, the competencies, tasks and emerging professional profiles of the journalist and the strategies for the formation of the profile in the digital transformation. The methodology applied for this research with a case analysis format, uses the qualitative-qualitative method, content analysis, to raise the state of the question and the categorized parameters and later to be applied through field research. To analyze the data, key public interviews were applied to the subject, such as: journalism professionals with a professional experience of more than ten years, who belong to the El Oro Association of Journalists (CPO) as well as to the most important media. . points of sale in the province; journalists with less than five years of experience, who began their professional practice with the much more consolidated digital era and exposed to more transformations; and experts in the area of national and international journalism and communication academics once with more than 20 years of experience in both areas. Regarding the quantitative analyzes, they have been raised with the application of surveys carried out to professionals in Social Communication graduated from the Technical University of Machala (UTMACH), taking into account the last two promotions that have less than five years of having obtained its title. job title. When talking about the results, it is verified that the competences and capacities of the professionals have been modified to the way of trying to be on a par with the demands, because within the new thing that they have had to assume, is the production of content for different supports and platforms in adaptive formats, being responsible for social networks and feeding content to blogs, among others, which has implied the challenge of adapting in a self-taught and formal way to the innovations that are presented, assuming the training It continues from a training strategy through YouTube tutorials to a few postgraduate preparations, in order not to be displaced or "forgotten" one way or another.
Lazo Serrano Lizette Ivonne
El presente trabajo de titulación se motiva, debido a que con la evolución digital existen cambios en el perfil de los diferentes profesionales de la comunicación; en el caso del quehacer periodístico, enfrenta una redefinición en su perfil vinculado a las transformaciones generadas por la evolución de las Tecnologías de la Información y la Comunicación (TIC) y como consecuencia la convergencia digital, lo cual implica que exista el dominio de nuevos lenguajes, competencias, conocimientos, habilidades y comportamientos, es por eso que es importante conocer cuáles son esos retos de los periodistas de la provincia de El Oro, en donde el periodismo digital ha tomado bastante terreno.. Teniendo en cuenta lo mencionado, la investigación denominada “Retos en el perfil profesional del periodista ante la transformación digital”, tiene como objetivo principal evaluar los retos actuales del periodista, ante la transformación digital que ha generado una redefinición en su perfil profesional y como objetivos específicos: identificar las competencias y las capacidades de los periodistas, conocer las necesidades de los profesionales y las acciones tomadas para desempeñar su trabajo, e identificar los retos que han asumido en su perfil profesional ante la transformación digital. Para la fundamentación teórica epistemológica, que es tomada como referencia del soporte de la investigación, se abordan los siguientes temas: transformación digital en el periodismo, etapas de la transformación tecnológica en el periodismo con la web 1.0, web 2.0, web 3.0 y web 4,0, los retos del ejercicio periodístico, el perfil profesional-académico del periodista en la transformación digital, las competencias, tareas y perfiles profesionales emergentes del periodista y las estrategias de formación del perfil en la transformación digital. La metodología aplicada para esta investigación con formato de análisis de caso, emplea el método cuali-cualitativo, análisis de contenidos, para levantar el estado de la cuestión y los parámetros categorizados y posterior a ser aplicados a través de la investigación de campo. Para el análisis de los dato se aplicaron entrevistas a públicos clave para el tema como: profesionales en periodismo con una experiencia profesional de más de diez años, que pertenecen al Colegio de Periodistas de El Oro (CPO) así como a medios de comunicación más importantes de la provincia; periodistas con menos de cinco años de experiencia, que iniciaron su ejercicio profesional con la era digital mucho más establecida y expuesta a más transformaciones; y expertos en el área del periodismo nacional e internacional y a la vez académicos de la comunicación con más de 20 años de experiencia en ambas áreas. En cuanto a los análisis cuantitativos se los ha levantado con la aplicación de encuestas realizadas a profesionales en Comunicación Social graduados de la Universidad Técnica de Machala (UTMACH), tomando en cuenta a las dos últimas promociones que tienen menos de cinco años de haber obtenido su título profesional. Al hablar de los resultados, se constata que las competencias y capacidades de los profesionales se han modificado a la forma de tratar de estar a la par con las exigencias, debido a que dentro de lo nuevo que han tenido que asumir, está el producir contenidos para diferentes soportes y plataformas en formatos adaptativos, el ser responsable de redes sociales y de alimentar contenido a blogs, entre otros, lo cual ha implicado el reto de adaptarse de forma autodidacta y de manera formal a las innovaciones que se presentan, asumiendo la formación continua desde una estrategia de formación a través de tutoriales de YouTube hasta pocas preparaciones de posgrado, para de una u otra manera no ser desplazados o “quedar en el olvido”.
Keywords: PERFIL PROFESIONAL; PERIODISMO DIGITAL; RETO PROFESIONAL; TRANSFORMACION DIGITAL